Hope to die : the Christian meaning of death and the resurrection of the body - Hahn, Scott; Chapman, Emily Stimpson (Emmaus Road Publishing, 2020)
"As Catholics, we believe in the resurrection of the body. We profess it in our creed. We?re taught that to bury and pray for the dead are corporal and spiritual works of mercy. We honor the dead in our Liturgy through the Rite of Christian burial. We do all of this, and more, because when Jesus Christ took on flesh for the salvation of our souls he also bestowed great dignity on our bodies. In Hope to Die: The Christian Meaning of Death and the Resurrection of the Body, Scott Hahn explores the significance of death and burial from a Catholic perspective. The promise of the bodily resurrection brings into focus the need for the dignified care of our bodies at the hour of death. Unpacking both Scripture and Catholic teaching, Hope to Die reminds us that we are destined for glorification on the last day. Our bodies have been made by a God who loves us. Even in death, those bodies point to the mystery of our salvation."--Publisher